Coaching philosophy and methods of Anatoly Tarasov: `Father` of Russian ice hockey - Bespomoshchnov, V. A.; Caron, J. G. (International Sport Coaching Journal, 2017)
Anatoly Tarasov was the architect of the Russian ice hockey system—one of the most storied program`s in the history of International ice hockey. As a head coach, he led his team to 3 Olympic gold medals, 9 World Championships, and 18 National Championships. He was also the first European inducted into the Hockey Hall of Fame in Canada. Given all that he accomplished, it is surprising that relatively little is known about Tarasov outside of Russia. The purpose of this paper is to introduce coach Tarasov and, through an analysis of his own writings and what others have written about him, shed some light on his coaching methods that we believe comprise his coaching philosophy. As we will demonstrate, Tarasov`s coaching methods, which would have been viewed as unusual at the time—particularly by ice hockey coaches in North America—are now widely supported in the coaching science literature and practiced by some of the world`s most regarded coaches. Rooted in Tarasov`s coaching methods, we also provide a number of "best practices" for ice hockey coaches, which we believe might also be applicable to coaches working in other contexts.